The financial performance of Amanah Saham Nasional (ASN) / Safra Diyana Roslan - Roslan, Safra Diyana (2010)
This report has been done to study The Financial Performance of Amanah Saham Nasional. This study using some sources like secondary data and other approaches such as financial ratio and gap analysis has been use as a data collection. The data is taken from external sources such as journal, internet and reference books. Result from this study, The Financial Performance for Amanah Saham Nasional (ASN) has a not well because of the economic downturn in year 2009. From the analysis also the ASN should have initiative to improve the efficiency and effectiveness of the Unit Trust Management Company. In this research, by using the financial ratio analysis we can determined the credit analysis, capital structure and return on investment. From the equation, we can interpret the performance of ASN through period of movement. In the 2009 the Malaysia economic still in recovery, the performance of the ASN is very bad, bit in the 2008 the performance of bank is very well compare the other previous years. It can look in the financial performance analysis. Besides that, this study was conducted to evaluate the cross sectional of financial ratios in the same industry. Results provide strong evidence that ASN perform differently than Amanah Mutual Berhad Dividend Trust Fund (AMBDTF) in year 2009. ASN had the poor performance and less consistent differences in credit analysis, capital structure and return on investment ratios. ASN are unsuccessful in making inefficient use of resources to balance their expenses in acquiring and acting on new information. There suggesting that as funds grow larger, they tend to become less efficient in their operations.